SAYAP PALACE MEMORIAL: RECONSTRUCTION OF THE LOST MALAY CULTURE - Asril, Asril; Faizah A.R, Hasnah; Elmustian, Elmustian; Hermandra, Hermandra (Paradigma: Jurnal Kajian Budaya, 2023)
The Sayap Palace is a relic of the Pelalawan Kingdom, located in Pelalawan Regency. This palace was built during the reign of Sultan Assyaidi Syarif Hasim. The purpose of this article is to describe the process of the establishment of the Sayap Palace, its role in people’s lives, and its use in the field of education. This article uses the historical method with descriptive analysis techniques and literature studies. After the end of the reign of the Pelalawan Kingdom, the Sayap Palace was no longer occupied and then collapsed. The Sayap Palace’s restoration took place twice, in 2003 and 2015. As a cultural heritage, the Sayap Palace has an essential meaning for the people of Pelalawan in particular and Riau in general. At the end of this article, we will also discuss how the Sayap Palace can be utilized in education.